Aware of the Future?: Development and Validation of the Futures Consciousness Scale - Fanny Lalot; Sanna Ahvenharju; Matti Minkkinen; Enrico Wensing (Hogrefe Publishing GmbH, 2022)
Futures Consciousness refers to the capacity that a person has for understanding, anticipating, and preparing for the future. Although the concept is widely used in the field of futures research, no quantitative tool exists yet that assesses it. Drawing from a recent five-dimensional model that considers Time perspective, Agency beliefs, Openness to alternatives, Systems perception, and Concern for others as interrelated sub-dimensions of a general construct of Futures Consciousness, we developed a composite 20-item scale that measures Futures Consciousness as an interindividual difference. The psychometric properties of this new scale were examined through a dual approach of exploratory and confirmatory factorial analyses with a total of 1,301 participants in three languages (English, French, and Finnish). The scale’s structure proved satisfactory and fitted the hypothesized five-dimensional model in all three languages. Measures of internal and external validity (convergent and concurrent) also indicated good psychometric properties. Notably, individuals’ scores were positively related to the adoption of several social future-oriented behaviors such as pro-environmental and civic behavior. As such, the developed scale proves a reliable tool that could be of use for scholars and practitioners in futures studies as well as psychology.